Educação De Jovens E Adultos (Eja) Na E.E. Profa. Alcides Rodrigues Aires Em Porto Nacional-To - ALENCAR, Viviane Ferreira De (Universidade Federal do Tocantins, 2023)
The present study presents as its theme the Education of Youth and Adults and as an object of study the offer of this type of education in the Profa State School. Alcides Rodrigues Aires, located in Setor Nova Capital, in Porto Nacional-TO, in 2019. The objectives of this study is to understand the process of offering this modality of education for young people and adults, mainly at the Escola Estadual Profa. Alcides Rodrigues Aires, in the year 2019 and identify the challenges faced by students and professors of this institution in relation to this type of teaching. The work had as its main reference the Pedagogical Political Project of the school institution. The school offers the three EJA segments, the 1st and 2nd being for people deprived of liberty, at the Temporary Prison House in Porto Nacional. It is noticed that one of the great challenges faced in the Education of Youth and Adults in this institution is school dropout and dropout.